Methicillin-Resistant Staphylococcus aureus Associated with Animals and Its Relevance to Human Health - Pantosti, Annalisa (Frontiers in Microbiology, 2012)
Staphylococcus aureus is a typical human pathogen. Some animal S. aureus lineages have derived from human strains following profound genetic adaptation determining a change in host specificity. Due to the close relationship of animals with the environmental microbioma and resistoma, animal staphylococcal strains also represent a source of resistance determinants. Methicillin-resistant S. aureus (MRSA) emerged fifty years ago as a nosocomial pathogen but in the last decade it has also become a frequent cause of infections in the community. The recent finding that MRSA frequently colonizes animals, especially livestock, has been a reason for concern, as it has revealed an expanded reservoir of MRSA. While MRSA strains recovered from companion animals are generally similar to human nosocomial MRSA, MRSA strains recovered from food animals appear to be specific animal-adapted clones. Since 2005, MRSA belonging to ST398 was recognized as a colonizer of pigs and human subjects professionally exposed to pig farming. The “pig” MRSA was also found to colonize other species of farmed animals, including horses, cattle and poultry and was therefore designated livestock-associated (LA)-MRSA. LA-MRSA ST398 can cause infections in humans in contact with animals, and can infect hospitalized people, although at the moment this occurrence is relatively rare. Other animal-adapted MRSA clones have been detected in livestock, such as ST1 and ST9. Recently, ST130 MRSA isolated from bovine mastitis has been found to carry a novel mecA gene that eludes detection by conventional PCR tests. Similar ST130 strains have been isolated from human infections in UK, Denmark and Germany at low frequency. It is plausible that the increased attention to animal MRSA will reveal other strains with peculiar characteristics that can pose a risk to human health.